Confirmation to start manufacturing of north zone escalator from level 10 to roof (01 pair) - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the confirmation to start manufacturing of north zone escalator from level 10 to roof of BRACU new campus building.